Orientação profissional: uma abordagem centrada na psicanálise de famílias - Gimenes, Aline Bertoli [UNESP]; Dias, Amanda Carvalho [UNESP]; Vecchiato, Bianca Savioli [UNESP]; Palma, Bruna Martins Veroni [UNESP]; Fernandez, Cerisa [UNESP]; Gigek, Thaís [UNESP]; Emídio, Thassia Souza [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The following article intends to introduce the project of an extension group in the psychology course on the development of activities with adolescents experiencing the career choosing moment. The proposal is to advise them in the construction of a professional identity project, seeking to offer a listening space, where the anxieties and anguishes related to the choosing process of each adolescent can be reflected and shared. From this listening, reflecting and problematizing space, teenagers potentialize themselves in front of the challenges, being able to look at the choosing moment with more clarity. As these teenager’s family resumption trigger device, which we believe is of great importance in this choosing process, we utilize the genogram technique, allowing the visualization of the career choices of each family member and the reflection on the history, choices and family group perspectives that affect this moment.

O presente trabalho tem por objetivo apresentar o projeto de um grupo extensionista do curso de psicologia no desenvolvimento de atividades com adolescentes que vivenciam o momento da escolha profissional. A proposta visa assessorá-los no processo de construção da identidade profissional, buscando oferecer um espaço de escuta onde as ansiedades e angústias relacionadas ao processo de escolha de cada adolescente possam ser refletidas e compartilhadas. A partir desse espaço de escuta, reflexão e problematização, os jovens se potencializam diante dos desafios, sendo capazes de olhar para o momento da escolha com mais clareza. Utilizamos a técnica do genograma como recurso para a retomada da história familiar desses jovens, que acreditamos ser de grande importância nesse processo de escolha, possibilitando a visualização das escolhas profissionais de cada familiar e a reflexão acerca da história, das escolhas e das perspectivas do grupo familiar que os afetam neste momento.
Keywords: Career orientation; Family; Psychoanalysis; Orientação profissional; Família; Psicanálise